The Creative Tension between the Universal Church and the Local Church - Kristiatmo, Thomas (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2023)
The universal dimension of the Church does not always go hand in hand with the fact that it has to manifest itself in a local community, that is to say, a local Church presided by a bishop. History has witnessed that sometimes there were tensions between the two. The solutions offered are oftentimes one-sided. One may become either a staunch defender of universality or a radical proponent of the local Church. However, neither of these two positions are fruitful for the growth of the Church worldwide among the faithful: while holding one dimension, one can easily overlook the other. Ecclesiology might have to explore different approaches that can relate these positions, bearing in mind the needs of the local Church and the fatihful. What is needed in dealing with the tension is creativity. The tension may never be resolved without being creative in exploring new ways of constructing local theologies.